Women Objectification in The Last Duel (2021) Film By Ridley Scott - Shania Andriana (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Women's objectification in film remains a critical issue, especially in narratives set within patriarchal societies. Ridley Scott’s The Last Duel (2021), which portrays a historical case of sexual violence, provides a compelling subject for examining how women’s experiences are represented. Objective: This study aims to analyze how the character Marguerite is objectified in the film The Last Duel, using both verbal and visual elements. Method: This qualitative research applies Martha Nussbaum's theory of objectification and Blain Brown's cinematography framework to examine dialogues and scenes involving Marguerite. Result: The film presents Marguerite through three narrative viewpoints: Jean de Carrouges, Jacques Le Gris, and Marguerite herself. While this technique provides a multifaceted look at events, it underrepresents Marguerite’s emotional depth and trauma as a sexual violence victim. Forms of objectification identified include instrumentality, denial of subjectivity, inertness, ownership, violability, and denial of autonomy. Conclusion: Marguerite's portrayal reflects the broader patriarchal values of 14th-century French society, where women's agency is suppressed, and their experiences are filtered through male perspectives. Contribution: This study contributes to feminist film criticism by highlighting the limitations of perspective-based storytelling in fully capturing women’s subjectivity, especially in narratives involving sexual violence.